Chitin biomass powered microbial fuel cell for electricity production using halophilic Bacillus circulans BBL03 isolated from sea salt harvesting area - Gurav, Ranjit; Bhatia, Shashi Kant; Choi, Tae Rim; Jung, Hye Rim; Yang, Soo Yeon; Song, Hun Suk; Park, Ye Lim; Han, Yeong Hoon; Park, Jun Young; Kim, Yun Gon; Choi, Kwon Young; Yang, Yung Hun (Bioelectrochemistry, 2019)
Incessant depletion of non-renewable energy sources has gained attention to search for new biological systems to transform organic biomass into electricity using microbial fuel cell (MFC). The main approach of the existing study was to develop a single step process to produce electrical energy from underutilized chitin biomass. Halophilic bacterium Bacillus circulans BBL03 isolated from anodic biofilm showed higher electricity production (26.508 μAcm2) in a natural seawater medium fed with 1.0% chitin. Maximum chitinase activity (94.24 ± 4.2 U mL−1) and N-acetylglucosamine (GlcNAc) production (136.30 ± 2.8 mg g−1 chitin) were achieved at 48 h. Prominent metabolites detected in chitin hydrolysis were lactate, formate, acetate, propionate, and butyrate. Furthermore, cyclic voltammetry (CV) studies revealed the possibility of direct electron transfer by anodic biofilm to anode without any external redox mediators. Polarization and coulombic efficiency (CE) analysis showed maximum power density (PD) 1.742 mWcm2 and 47% CE using 1% chitin as a substrate. Alteration in crystallinity and functional group on chitin were analysed using FTIR and XRD. Therefore, natural seawater-chitin powered MFCs could be a cheap asset for longer electricity production.
Keywords: Bacillus circulans; Chitinase activities; Coulombic efficiency; Direct electron transfer; Electricity production; Halophilic; Maximum power density; Non-renewable energy sources; Bacillus; Bioelectric Energy Sources; Biofilms; Biomass; Chitin; Electricity; Electrodes; Equipment Design; Seawater; Bacillus circulans BBL03; Chitin; Electricity; Halophilic; Microbial fuel cell